Intrinsic stability of magnetic anti-skyrmions in the tetragonal inverse Heusler compound Mn1.4Pt0.9Pd0.1Sn - Rana Saha (Nature Portfolio, 2019)
Magnetic anti-skyrmions—chiral spin textures that could find applications in spintronics—have been recently observed in inverse tetragonal Heusler Mn1.4Pt0.9Pd0.1Sn. Here, the authors observe anti-skyrmions in thin films of Mn1.4Pt0.9Pd0.1Sn over a wide range of temperature and magnetic fields.